2021
DOI: 10.1007/s43678-021-00159-y
|View full text |Cite|
|
Sign up to set email alerts
|

External validation of a low HEAR score to identify emergency department chest pain patients at very low risk of major adverse cardiac events without troponin testing

Abstract: Background The history, ECG, age, risk factor (HEAR) score has been proposed to identify patients at sufficiently low risk of acute coronary syndrome that they may not require troponin testing. The objective of this study was to externally validate a low HEAR score to identify emergency department (ED) patients with chest pain at very low risk of 30-day major adverse cardiac events (MACE). Methods This was a secondary analysis of a prospective cohort of patients requiring troponin testing to rule out myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
2
11
0
2
Order By: Relevance
“…We tried to communicate with the corresponding authors of the abstracts via email for their published studies in full text, but received only studies that were already included. Therefore, 10 studies were finally included and considered eligible for systematic review and analysis [9,10,33–40] (Supplementary Figure 1, Supplemental digital content 2, http://links.lww.com/EJEM/A332 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We tried to communicate with the corresponding authors of the abstracts via email for their published studies in full text, but received only studies that were already included. Therefore, 10 studies were finally included and considered eligible for systematic review and analysis [9,10,33–40] (Supplementary Figure 1, Supplemental digital content 2, http://links.lww.com/EJEM/A332 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this systematic review, 33 843 patients were included from 10 studies [9,10,33–40]. Five studies were conducted in Europe [9,33,34,38,40], one in Asia [37], and the rest in North America [10,35,36,39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, questions remain, including the additional value of risk scores over high-sensitivity troponin testing alone 1. In this secondary analysis of 1150 prospectively recruited patients, O’Reilly et al sought to externally validate the HEAR score (HEART score minus troponin) and estimate the proportion of patients who could be safely discharged from the ED without any troponin assay 2. They found that a HEAR score of ≤1 identified 17.6% of patients as very low risk for any major adverse cardiac event (MACE) up to 30 days, with a sensitivity of 99.2% (95% CI 95.6% to 99.9%).…”
Section: External Validation Of a Low Hear Score To Identify Emergenc...mentioning
confidence: 99%